Buddhism and Tourism: A Study of Lumbini, Nepal (Journal of Tourism and Hospitality Education, 2020)
Buddhism is one of the major religions in the world. About four hundred million Buddhist people and millions of peace lovers around the globe admire to visit the holy places following the footsteps of the Buddha as the Buddha himself enshrined pilgrimage as an important act in the life of a peace seeker. Peace and happiness are the main pursuit of people longing for, but in many ways they are starving. Buddhism has been source and way forward for peace and happiness- this is how people have started realizing today. In pursuit of peace, billions of dollars worth Buddha images, Buddhist souvenirs and puja paraphernalia are sold every year in Buddhist sites of different countries that make local economy vibrant. There are many Buddhist heritage sites that have been explored, excavated, conserved, developed and promoted because of tourism activities all over the world. But very few studies have been done, so far, to understand relation between Buddhism and tourism. This study examines the relation between Buddhism and tourism in the context of Greater Lumbini Area, Nepal for planning, development, promotion and educative purpose. The findings of present study reveal that there is “complementary and positive relation between Buddhism and tourism”. It means promotion of Buddhism helps develop quality tourism in the GLA vis-à-vis development of tourism in the region promotes Buddhism and Buddhist sites.